TEACHER’S EXPERIENCES OF ONLINE ASSESSMENT IMPLEMENTATION IN TEACHING ENGLISH - I Wayan Adi Widnyana; I Gede Yoga Permana; Pande Gede Artha Pratama (IKIP Siliwangi, 2023)
This study aimed to identify the experience of teachers in implementing online assessments in the process of teaching and learning English at SMK TI Bali Global Singaraja. This study was designed using a descriptive qualitative research method. The data were collected by interview documentation and also observation. This study used the technique of analyzing the data Miles and Huberman Data Analysis which has three phases; (1) data condensation or data reduction, (2) data display (3) drawing and conclusion verification. The results of this study indicated that the English teacher has implemented online assessment through several platforms such as Google Classroom, Instagram, and also lmssmkti.com as the main platform for assessing all skills in English. There were advantages, disadvantages, and difficulties faced by the teacher in implementing online assessment. The difficulties that could be obtained consist of technical and non-technical difficulties both from students and teachers such as internet constraints and teachers who had difficulty using the online assessment platform for the first time, besides many students complained about difficulties using platforms for online assessments. This research was expected to be useful for future researchers in carrying out similar research with different method, instruments and also samples.